2018
DOI: 10.3389/fmicb.2018.00407
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of blaNDM Variants Among Enterobacteriaceae From a Neonatal Intensive Care Unit in a Northern India Hospital

Abstract: Carbapenem-resistance among enterobacteriaceae has become a global health concern. The objective of this study was to understand NDM producing enterobacteriaceae and their genetic basis of resistance, spreading in neonatal intensive care unit. Carbapenem resistant NDM producing enterobacteriaceae isolates were recovered from rectal swab and blood sample of infants admitted in NICU. These were determined by using Carba-NP test. All isolates were identified using BD PhoenixTM−100 and MICs were determined by brot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
54
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 44 publications
3
54
0
Order By: Relevance
“…Most of NDM-5 producers were identified as ST48 (90%; 27/30). NDM-5 has mostly been found in E. coli , 27 and this is the first reported outbreak of NDM-5-producing ST48 K. pneumoniae in China. In addition, KPC-2, the predominant carbapenemase among adults in China, was detected in isolates from patients in the PICU and charity ward, and most of these isolates belonged to ST11, which is different from the pandemic sequence type ST258.…”
Section: Discussionmentioning
confidence: 88%
“…Most of NDM-5 producers were identified as ST48 (90%; 27/30). NDM-5 has mostly been found in E. coli , 27 and this is the first reported outbreak of NDM-5-producing ST48 K. pneumoniae in China. In addition, KPC-2, the predominant carbapenemase among adults in China, was detected in isolates from patients in the PICU and charity ward, and most of these isolates belonged to ST11, which is different from the pandemic sequence type ST258.…”
Section: Discussionmentioning
confidence: 88%
“…bringing about problems regarding treatment and control. Our previous study showed that bla NDM gene had disseminated in the NICU via different Gram-Negative Bacilli (E. coli, Citrobacter freundii, Citrobacter braakii, Klebsiella oxytoca, Enterobacter cloacae, Enterobacter aerogenes) harboring blaNDM [15]. An earlier study reported that the blaNDM is carried by various types of plasmids incompatibility such as IncA/C, IncF, IncN, IncL/M or untypable/IncR, and is rarely found to be chromosomally integrated [13].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, one of the major reasons for the rapid emergence and spread of NDM-5 is its location on different incompatibility typing plasmids (Feng et al, 2018;Wang et al, 2018). Various plasmid incompatibility typing groups carrying bla NDM−5 have been reported worldwide with the most prevalent being IncFIA/B and IncX3 in Korea (Baek et al, 2019), IncFIA and IncFIB in Egypt (Gamal et al, 2016), IncFIA and IncFK in India (Ahmad et al, 2018), and IncFII in the United States (Rojas et al, 2017). Previous studies in China have shown several sporadic cases of clinical infections linked to ST167-type E. coli carrying the bla NDM−5 gene, which was mainly located on the IncX3 plasmid (Chen et al, 2014;Yang et al, 2014;Li et al, 2018;Sun et al, 2019).…”
Section: Introductionmentioning
confidence: 99%